Parasites and Raven Mothers: A German-Japanese Comparison on (Lone) Motherhood - Anna Klabunde; Evelyn Korn (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Having a child out of wedlock used to be associated with shame and scorn. This is mostly not the case anymore in the western world. Therefore, freed from social sanctions, single motherhood has become an additional family-choice alternative for women, along with marriage and childlessness. Yet, the institutions that influence women's decisions differ across countries. We compare the institutional frame, in particular labor-market characteristics and family law, in Germany and Japan and, in addition, the interaction between culture and institutions. Both countries had a very traditional (one-earner) family system until the second half of the 20th century. Now we can observe that social changes that happened in Germany decades ago are happening only now in Japan. We analyze if and how the consequences in terms of family structures and fertility rates that resulted in Germany can be transfered to Japan. – – Dieser Artikel vergleicht die institutionellen Rahmenbedingungen in Deutschland und Japan, die die Fertilitätsentscheidung von Frauen beeinflussen können. Wir richten unser Augenmerk speziell auf Familienrecht, Arbeitsmarktcharakteristika und die Interaktion zwischen Institutionen und kulturellen Faktoren. Daraus leiten wir Implikationen für die relative Attraktivität von Ehe und Mutterschaft in beiden Ländern ab. Wir stellen fest, dass soziale Veränderungen, die in Deutschland vor einigen Jahrzenten vor sich gingen - insbesondere die Aufweichung der traditionellen Alleinverdiener-Familie - in Japan derzeit passieren. Wir analysieren, ob sich die Konsequenzen für Familienstruktur und Geburtenrate von Deutschland auf Japan übertragen lassen.
Keywords: D10; J13; J18; K36; 330; out-of-wedlock childbearing; fertility; family law; Germany; Japan